The Role of Parenting Patterns in Supporting Child Development Child Cognitive - Junaidin Junaidin; Sri Nurhayati (FASHLUNA, 2026)
Children's cognitive development is a fundamental aspect in the formation of thinking, understanding, and problem-solving abilities, which is greatly influenced by the family environment, particularly parental parenting styles. To date, studies of cognitive development have focused more on the context of formal education, while the role of parenting styles within the family environment has not received adequate attention. This study aims to analyze the role of parental parenting styles in supporting the cognitive development of elementary school-aged children and to identify parenting factors that contribute to optimizing children's thinking abilities. This study uses a qualitative approach with a phenomenological method to understand the experiences and practices of parenting parents in everyday life. The study was conducted at SDN 45, Bima City, involving parents of students aged 7–12 years. Data were collected through in-depth interviews, participatory observation, and documentation studies. Then, data were analyzed through data reduction, data presentation, and conclusion drawing using triangulation techniques. The results show that parenting styles characterized by effective communication, cognitive stimulation, active parental involvement in children's learning activities, and consistent emotional support play an important role in improving children's attention, memory, problem-solving skills, and logical thinking. Conversely, parenting styles that lack interaction and stimulation tend to hinder children's cognitive development. This research confirms that parenting styles are the primary foundation for supporting children's cognitive development and need to be integrated into efforts to improve the quality of family-based education.